The Differential Geometry of the Orbit Space of Extended Affine Jacobi Group A₁ - Almeida, Guilherme F. (Symmetry, Integrability and Geometry: Methods and Applications, 2021)
We define certain extensions of Jacobi groups of A₁, prove an analogue of the Chevalley theorem for their invariants, and construct a Dubrovin-Frobenius structure on their orbit space.